2008
DOI: 10.3748/wjg.14.7149
|View full text |Cite
|
Sign up to set email alerts
|

Role of chemokines and their receptors in viral persistence and liver damage during chronic hepatitis C virus infection

Abstract: Chemokines produced in the liver during hepatitis C virus (HCV) infection induce migration of activated T cells from the periphery to infected parenchyma. The milieu of chemokines secreted by infected hepatocytes is predominantly associated with the T-helper cell/Tc1 T cell (Th1/Tc1) response. These chemokines consist of CCL3 (macrophage inflammatory protein-1 alpha; MIP-1 alpha), CCL4 (MIP-1 beta), CCL5 (regulated on activation normal T cell expressed and secreted; RANTES), CXCL10 (interferon-gamma-inducible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
102
1
8

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(118 citation statements)
references
References 80 publications
7
102
1
8
Order By: Relevance
“…These findings suggest that a large number of inflammatory pathways and mechanisms are operant in patients destined not to survive PALF, leading to a state of selfsustaining or self-propagating inflammation driven by both innate and T cell-dependent mechanisms. reported in liver failure 27,28 , and circulating levels of both chemokines have been implicated in chronic hepatitis C 29 . We have shown that MCP-1 is a central node in hepatocyte inflammatory responses to stress, a role perhaps related to the ability of circulating MCP-1 levels to segregate outcomes in human blunt trauma 15 .…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that a large number of inflammatory pathways and mechanisms are operant in patients destined not to survive PALF, leading to a state of selfsustaining or self-propagating inflammation driven by both innate and T cell-dependent mechanisms. reported in liver failure 27,28 , and circulating levels of both chemokines have been implicated in chronic hepatitis C 29 . We have shown that MCP-1 is a central node in hepatocyte inflammatory responses to stress, a role perhaps related to the ability of circulating MCP-1 levels to segregate outcomes in human blunt trauma 15 .…”
Section: Discussionmentioning
confidence: 99%
“…By binding CD81, the HCVe2 protein has been shown to induce RANTES-CCL5 expression by T cells, whereas overexpressed RANTES-CCL5 binds the CCR5 receptor, which results in receptor internalization. This reduction in the levels of chemokine receptors associated with cytotoxic responses in T cells may impair the chemotaxis of these cells to the liver and allow for viral persistence [19,20]. The primary cellular defense mechanism active during HCV infection is the synthesis of antiviral cytokines such as type I interferon (IFN α/β).…”
Section: Hepatitis C Virus and Cytokine Productionmentioning
confidence: 99%
“…Thus a Th1 chemokine receptor set can be defined: CCR5 and CXCR3; while CCR3, CCR4 and CCR8 are linked to Th2 responses (Larrubia et al, 2008). Therefore, in a viral infection a certain subset of chemokines are especially interesting, as the Th1 response is considered the adequate and efficient response type.…”
Section: Chemokines In the Adaptive Immune Responsementioning
confidence: 99%